Perceptions of effective facebook advertising and its relation to consumers' decision to buy. - Wong, Lily (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The objective of this study is to examine the perception of consumers based on the Six-factor Facets Model of Effect and social factors toward the effectiveness of Facebook advertising and its relation to their decision to buy. As a result, seven (7) hypotheses were developed. A total of 500 questionnaires have been distributed to students of Universiti Malaysia Sarawak (UNIMAS) and 463 questionnaires have been successfully collected and analysed using Pearson correlation and simple linear regression The results have supported all seven (7) hypotheses. In conclusion, this study has confirmed that consumers' response toward Facebook advertising and effect of their social factors have significant impacted on their decision to buy. Nevertheless, this study demonstrated that a persuasive advertising message via Facebook and influence of social factors are the strongest determinants on consumer's decision to buy.